Mantle Cell Hyperplasia of Peripheral Lymph Nodes as Initial Manifestation of Sickle Cell Disease - Monabbati, Ahmad; Noori, Sadat; Safaei, Akbar; Ramzi, Mani; Eghbali, Seyedsajjad; Adib, Ali (Case Reports in Hematology, 2016)
Sickle cell disease (SCD) is a well known hemoglobinopathy with usual manifestations including anemia, hyperbilirubinemia, and vasoocclusive complications. Despite presence of mild splenomegaly in early phase of the disease, lymphadenopathy is not an often finding of SCD. We introduce an undiagnosed case of SCD who presented in third decade of his life with multiple cervical lymphadenopathies and mild splenomegaly persistent for about five years. Histopathologic examination of the resected lymph nodes showed expansion of the mantle cell layers of secondary follicles as well as several monomorphic mantle cell nodules. To rule out possibility of a malignant process involving lymph nodes, an immunohistochemical panel was ordered which was in favor of benign mantle cell hyperplasia. Immunoglobulin gene rearrangement study showed no clonal bands and confirmed benign nature of the process. Respecting mild abnormalities on Complete Blood Count, peripheral blood smear was reviewed revealing some typical sickle red blood cells as well as rare nucleated red blood cells. Solubility test for hemoglobin (HB) S was positive. Hemoglobin electrophoresis confirmed diagnosis of homozygous HbS disease.